Validation of the American English Acute Cystitis Symptom Score - Jakhongir F. Alidjanov; Kurt G. Naber; Adrian Pilatz; Florian M. Wagenlehner (MDPI AG, 2020)
The diagnosis of acute uncomplicated cystitis (UC) is usually based on clinical symptoms. The study aims to develop and validate the American-English Acute Cystitis Symptom Score (ACSS), a self-reporting questionnaire for diagnosis and patient-reported outcome in women with acute uncomplicated cystitis (UC). After certified translation into American-English and cognitive assessment, the clinical validation of the ACSS was performed embedded in a US phase-II trial. 167 female patients with typical symptoms of UC were included in the study following US Food and Drug Administration (FDA) guidance. At Day 1 (diagnosis), the mean (SD) sum score of the six ACSS typical symptoms reached 10.60 (2.51). Of 100 patients followed-up last time on Day 5 or 6 (End-of-treatment, EoT), 91 patients showed clinical success according to the favored ACSS criteria (sum score of typical symptoms 0.98 (1.94)). There was no correlation between the severity of symptoms on Day 1 or between clinical success rate at EoT and level of bacteriuria on Day 1. The American-English ACSS showed high predictive ability and responsiveness and excellent levels of reliability and validity. It can now be recommended as the new master version in clinical and epidemiological studies, in clinical practice, or for self-diagnosis of women with symptoms of UC.